Aspek Mitologi dalam Novel Gadis Kretek Ditinjau dari Teori Strukturalisme Lèvi-Strauss - Alfiyyah Sausan Mashuri; Arina Alhaq; Arinda Safira; Aulia Nikmatul Fauziah; Dini Afriyanti; Ikfina Izzatul Malikhah; Suryo Ediyono (Jurnal Empirika, 2024)
This study aims to analyze the mythological (mytheme) aspects of Javanese culture contained in the novel "Gadis Kretek" by Ratih Kumala. The myths are studied using the Lèvi-Strauss structuralism approach. This study uses a descriptive qualitative method. The analysis method used is structuralism. The study results indicate several Javanese mythologies raised in the novel, namely mend ari-ari, fortune-telling by a clever person and meditation on Mount Kawi. These myths have different meanings and functions in the story. This study also shows that Javanese mythology in the novel "Gadis Kretek" not only complements the story but also has a deep meaning about Javanese cultural values. These myths provide an overview of how Javanese people view the world and interpret various life events. This study also discusses the relationship between episodes and characters in the novel "Gadis Kretek". Each part of the episode and the characters in this novel are interrelated to create a structure.